SOURCES OF INFORMATION USED BY CASSAVA PROCESSORS IN DELTA STATE - Amaechi, U. G.; Ugboh, O.; Ovharhe, O. J.; Ajieh, P. C. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the various sources of information accessed by cassava processors in Delta State, Nigeria. The primary objective was to identify the main channels through which these processors receive information related to cassava processing. Data were gathered using a structured interview questionnaire administered to a purposive sample of 106 out of 349 cassava processors. Findings show that 92% of respondents rely on fellow cassava processors for information on processing technologies. Additionally, majority (82%, 70% and 62%) obtain information from extension agents, radio broadcasts, and family and friends, respectively. Other sources of information used by the respondents include neighbors (21%), television (14%), and friends (39%), while 10% cited an unclear source ("9"), 3% mentioned sales agents, and none reported using bulletins, pamphlets, or seminars The study revealed that most cassava processors were women, with many being married and literate, and an average age of 34. However, a large proportion lacked cooperative membership, indicating low participation in support networks. The study indicates that cassava processors largely rely on informal and easily accessible sources—such as fellow processors, extension agents, and radio—for agricultural information. This highlights the significant role of social networks and mass media in disseminating knowledge within rural communities. However, the limited use of formal sources like newspapers, online platforms, and printed materials—which typically require literacy—points to educational constraints. Women constitute the majority of cassava processors, and while many are married and possess basic literacy, low participation in cooperatives limits their access to shared resources and support. These findings emphasize the need to strengthen extension services and implement inclusive, gender-sensitive, and education-focused policies that promote cooperative participation and enhance rural productivity.